Transnational Organized Crime: dalam Perspektif Hukum Pidana dan Kriminologi - Harkrisnowo, Harkristuti (Indonesian Journal of International Law, 2021)
Transnational organized crime has become a burning issue for the international community the past decade. Money laundering, human trafficking, drug trafficking, terrorism and firearms smuggling are examples of illicit dealing committed by organized criminal groups for their material or other gain at the expense of the rest of the society. The evasiveness and complicity of illegal organizations committing such crimes have compelled the United Nations to adopt a number of conventions including their protocols in order to combat their widening activities. Indonesia is taking similar steps, especially through legislative measures, despite the desperate conditions faced by the nations in term of law enforcement in general. Nonetheless, as victim of a number of crimes, which, among others, are alleged, to have been committed by transnational organized criminal, Indonesia is in dire need to take more serious measures in addition to legislative ones, including international and regional cooperations. Eventhough such decisions are in the hands of the ruling elite, the role of public, particularly the civil society should not be neglected.